Management of Tinnitus The Enriching Views of Treatment Options - Wang, Tang-Chuan (IntechOpen, 2019)
Tinnitus ("ringing in the ears") is a serious health condition that can negatively affect a patient's quality of life. Although there is presently no way to cure tinnitus, there are some good, well-established methods that can significantly reduce the burden of tinnitus. Importantly, the only way to success is to understand the detailed knowledge offered by clinicians and researchers. Based on these concepts, the book incorporates updated developments as well as future perspectives in the ever-expanding field of tinnitus. This book can also serve as a reference for persons involved in this field whether they are clinicians, researchers, or patients. Once we've integrated the views of various disciplines and treatment options, we can go forth to manage tinnitus well.